Does subsidized childcare help poor working women in urban areas? evaluation of a government-sponsored program in Guatemala City - Ruel, Marie T.; de la Briere, Benedicte; Hallman, Kelly; Quisumbing, Agnes R.; Coj de Salazar, Nora (International Food Policy Research Institute, 2002)
High urbanization rates in Latin America are accompanied by an increase in women’s participation in the labor force and the number of households headed by single mothers. Reliable and affordable childcare alternatives are thus becoming increasingly important in urban areas. The Hogares Comunitarios Program (HCP), established in Guatemala City in 1991, was a direct response to the increasing need of poor urban dwellers for substitute childcare. This government-sponsored pilot program was designed as a strategy to alleviate poverty by providing working parents with low-cost, quality childcare within their community. This paper presents preliminary findings from an evaluation of the HCP carried out in 1998 in urban slums of Guatemala City. The evaluation included both an operations (or process) evaluation and an impact evaluation. Key findings of the operations evaluation are summarized, and preliminary findings of the impact evaluation on children’s dietary intakes are presented. Aspects related to the targeting, coverage, and cost of the program are also discussed, and the patterns of childcare use by nonbeneficiary households and their costs are described.